2008
DOI: 10.1007/s10327-008-0117-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene coding for SigA-binding protein from Arabidopsis appears to be transcriptionally up-regulated by salicylic acid and NPR1-dependent mechanisms

Abstract: SigA-binding protein (SIB A) is a nuclearencoded chloroplast-targeted protein that interacts with the plastid-encoded plastid RNA polymerase r-factor SigA (Sig1). In this study, the SIB A gene responded rapidly to salicylic acid (SA) treatment, but responded slowly to ethylene (ET) and jasmonic acid (JA) treatments as determined with microarray and quantitative real-time RT-PCR analyses. Expression of the SIB A gene increased rapidly, with a peak at 2 h after SA treatment and then decreased gradually. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Thus, VQ23 positively regulates the plant defense response against both necrotrophic and biotrophic pathogens likely via a WRKY-dependent signaling pathway. However, it was reported that VQ23 overexpression plants do not differ from the control with respect to their sensitivity to the virulent strain P. syringae pv tobacco (Pst) DC3000 (Narusaka et al, 2008). VQ16/SIB2 plays a redundant role in response to B. cinerea infection with VQ23 (Lai et al, 2011), consistent with their evolutionary relatedness in VQ group VI.…”
Section: Structural Features Of Vq Proteinsmentioning
confidence: 64%
See 1 more Smart Citation
“…Thus, VQ23 positively regulates the plant defense response against both necrotrophic and biotrophic pathogens likely via a WRKY-dependent signaling pathway. However, it was reported that VQ23 overexpression plants do not differ from the control with respect to their sensitivity to the virulent strain P. syringae pv tobacco (Pst) DC3000 (Narusaka et al, 2008). VQ16/SIB2 plays a redundant role in response to B. cinerea infection with VQ23 (Lai et al, 2011), consistent with their evolutionary relatedness in VQ group VI.…”
Section: Structural Features Of Vq Proteinsmentioning
confidence: 64%
“…The transcription of VQ genes is modulated by multiple endogenous and environmental signals, consistent with their diverse roles in stress responses and during plant growth and development. For instance, B. cinerea infection and SA treatment rapidly and strongly induce VQ23 and VQ16 transcript levels (Narusaka et al, 2008;Xie et al, 2010;Lai et al, 2011). VQ22 transcript is significantly increased upon JA treatment and quickly accumulates after mechanical wounding (Hu et al, 2013a).…”
Section: Regulation Of Vq Proteinsmentioning
confidence: 99%
“…Accumulating studies suggest that members of the VQ family play diverse functions, such as regulating the plant defense response (Andreasson et al, 2005;Narusaka et al, 2008;Xie et al, 2010;Lai et al, 2011), abiotic stress resistance (Perruc et al, 2004;Hu et al, 2013), and seed development (Wang et al, 2010). Our study provides genetic and molecular evidence that VQ29 has a prominent role in plant growth and development in response to the light environment, thus extending the functionality of this plant-specific protein family.…”
Section: Vq29 Defines a Novel Repressor Of Seedling Deetiolationmentioning
confidence: 80%
“…The functions of a few members of this family has been characterized to date. For example, SIGMA FACTOR BINDING PROTEIN1 (SIB1/VQ23), its close homolog SIB2 (VQ16), and MITOGEN-ACTIVATED PROTEIN KINASE4 SUB-STRATE1 (VQ21) are required for the plant defense response (Andreasson et al, 2005;Narusaka et al, 2008;Xie et al, 2010;Lai et al, 2011). In addition, HAIKU1 (VQ14) is a regulator of endosperm growth and seed size (Wang et al, 2010), while CALMODULIN-BINDING PRO-TEIN25 (VQ15) and VQ9 function as negative effectors of osmotic and salinity stress tolerance, respectively (Perruc et al, 2004;Hu et al, 2013).…”
mentioning
confidence: 99%
“…In B. cinereainfected plants, the transcript levels of SIB1 and SIB2 were markedly enhanced, similar to those of WRKY33 (Figure 7). SIB1 is also induced by SA and the bacterial pathogen P. syringae (Narusaka et al, 2008;Xie et al, 2010). Pathogen-induced Figure 6.…”
Section: Sib1 Does Not Significantly Affect the Transcription-activatmentioning
confidence: 99%